Inhibitory Effect of Sulfated Polysaccharide from Codium edule P.C. Silva Against 2,4-Dinitrofluorobenzene (DNFB)- Induced Allergic Contact Dermatitis on Female BALB/c Mice - Martin Raemond Brondial Mallabo; Mary Jho - Anne T. Corpuz; Reginald B. Salonga; Ross D. Vasquez (Tabriz University of Medical Sciences, 2022)
Purpose: Sulfated polysaccharide from Codium species has been reported for its antiinflammatoryactivities. However, the effect of sulfated polysaccharide from Codium edule onallergic responses has not been studied. The study was conducted to determine the effect ofsulfated polysaccharide (F1) from C. edule on allergic contact dermatitis (ACD) induced by2,4-dinitrofluorobenzene (DNFB) in female BALB/c mice.Methods: F1 was isolated using DEAE sepharose gel chromatography and chemically identifiedby LC-MS analyses. The effects of F1 on changes in ear thickness, allergic responses, andhistology were evaluated. The effects of F1 on the production of inflammatory cytokinesinterferon gamma (IFN-γ) and tumor necrosis factor-alpha (TNF-ɑ) in serum were also quantifiedand compared with standard prednisolone therapy.Results: F1 was identified as a heteropolysaccharide with β-D-galactans and β-L-arabinans units.F1 was non-toxic at 2000 mg/kg. Administration of F1 in DNFB-challenged mice significantlysuppressed the increase in ear thickness, erythema, desquamation, and proliferation ofinflammatory cells. F1 significantly decreased the production of inflammatory markers, IFN-γand TNF-α in a dose-dependent manner when compared to the untreated group (P<0.05).Conclusion: Results suggest that F1 from C. edule is a bioactive sulfated heteropolysaccharidewith anti-inflammatory activity and might be a valuable candidate molecule for the treatmentof allergic diseases such as ACD.